Penggunaan Media Audio Visual untuk Meningkatkan Keterampilan Menyimak Siswa SMK Negeri 6 Bandar Lampung - Abdulloh, Abdulloh; Surastina (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2025)
This research aims to improve listening skills using audio-visual media for students at SMK Negeri 6 Bandar Lampung. This classroom action research involves simultaneous collaboration between the researcher and several parties, including the school principal, classroom teachers, and fellow researchers. The study consists of two cycles, with each cycle having three meetings. The research method used is classroom action research (CAR). The subjects of this study were 10th-grade students at SMK Negeri 6 Bandar Lampung. The study population was 56 students, and the entire population was used as the sample, making the sample size 56 students. Data collection methods included observation checklists, interviews, and documentation. The data were analyzed using both descriptive qualitative and quantitative techniques. The research findings indicate that the use of audio-visual media is effective in improving the fantasy story listening skills of 10th-grade students at SMK Negeri 6 Bandar Lampung. This is evident from the research results, which showed that students' listening skills in the pre-cycle only had an average score of 37.32, which is categorized as poor. During the first cycle of intervention, students' listening skills improved to 49.28, which is in the sufficient category. Subsequently, in the second cycle, the score reached 64.82, which is categorized as good.